Fondi In Focus: Boost Student’s Vocabulary Mastery in Senior High School - Rahma Pebriyanti; M. Sofian Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study investigates the effectiveness of the Fondi application in enhancing students’ English vocabulary acquisition at the senior high school level. A quantitative method with a pre-experimental one-group pre-test and post-test design was employed. The research was conducted at SMA Negeri 1 Rumpin, Bogor, involving 27 tenth-grade students selected through cluster sampling. Data were collected through pre-test and post-test instruments and analysed using the Wilcoxon Signed-Rank Test. The findings revealed that the mean pre-test score was 44.48, while the mean post-test score increased to 71.25. The statistical analysis yielded a Z value of -4.542 with a significance level of 0.000 (<0.05), indicating a significant difference between the pre-test and post-test results. Consequently, the alternative hypothesis (H1) was accepted, confirming that the Fondi application effectively enhances students’ vocabulary mastery.